Dynamic ginsenoside-sheltered nanocatalysts for safe ferroptosis-apoptosis combined therapy. (1st October 2022) - Zhao, Xiaoxiong; Wu, Jicheng; Guo, Danjing; Hu, Shen; Chen, Xiang; Hong, Liangjie; Wang, Junmei; Ma, Jugang; Jiang, Yangkang; Niu, Tianye; Miao, Fenglin; Li, Wengang; et al.
Abstract: Chemodynamic therapy (CDT)-activated apoptosis is a potential anticancer strategy. However, CDT encounters a bottleneck in clinical translation due to its serious side effects and low efficacy. Here, we first reveal that surface engineering of ginsenoside Rg3 dramatically alters the organ distribution and tumor enrichment of systematically administered nanocatalysts using the orthotopic pancreatic tumor model while avoiding toxicity and increasing efficacy in vivo to address the key and universal toxicity problems encountered in nanomedicine. Compared with nanocatalysts alone, Rg3-sheltered dynamic nanocatalysts form hydrophilic nanoclusters, prolonging their circulation lifespan in the blood, protecting the internal nanocatalysts from leakage while allowing their specific release at the tumor site. Moreover, the nanoclusters provide a drug-loading platform for Rg3 so that more Rg3 reaches the tumor site to achieve obvious synergistic effect with nanocatalysts. Rg3-sheltered dynamic nanocatalysts can simultaneously activate ferroptosis and apoptosis to significantly improve anticancer efficacy. Systematic administration of ginsenoside Rg3-sheltered nanocatalysts inhibited 86.6% of tumor growth without toxicity and prolonged the survival time of mice. This study provides a promising approach of nanomedicine with high biosafety and a new outlook for catalytic ferroptosis-apoptosis combined antitumor therapies. Statement of significance: Chemodynamic therapy (CDT) has limited clinical efficacy in cancer. In this study, we developed Rg3-sheltered dynamic nanocatalysts, which could simultaneously activate ferroptosis based on CDT-activated apoptosis, and ultimately form a combined therapy of ferroptosis-apoptosis to kill tumors. Studies have shown that the nanocatalysts after Rg3 surface engineering dramatically alters the pharmacokinetics and organ distribution of the nanocatalysts after being systematically administered, resulting in avoiding the toxicity of the nanocatalysts. Nanocatalysts also act as a drug-loading platform, guiding more Rg3 into the tumor site. This study emphasizes that nanocatalysts after Rg3 surface engineering improve the safety and effectiveness of ferroptosis-apoptosis combined therapy, providing an effective idea for clinical practices. Graphical abstract: Image, graphical abstract